Study and Conclusion of the Relationship Between Social Conflicts and Social Philosophical Interpretation (Eurasian Journal of Humanities and Social Sciences, 2023)
The article presents an overview of modern approaches to the study of social conflicts, including a structural approach, a conflictological approach, and socio-philosophical theory. The authors analyze the causes and mechanisms of social conflicts, their role in changing social relations and the consequences for social stability. The main attention in the article is paid to the socio-philosophical interpretation of social conflicts. The authors explore the role of values, ideologies and philosophical concepts in the formation and resolution of conflicts in society. They analyze how different philosophical schools of thought influence the interpretation of social conflicts and how these interpretations can influence their resolution. As a result of the study, the authors come to the conclusion about the relationship between social conflicts and sociophilosophical interpretation. They emphasize that understanding social conflicts through the prism of philosophical ideas and values can significantly influence their resolution and social dynamics. The authors propose further research in this area in order to better understand the interaction between social conflicts and sociophilosophical interpretation